Civil Legal Actions Against Criminal Activities Under the Age of Theft - J. E. Melky Purba (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Children as perpetrators of criminal acts must be treated specifically, some provisions protect children, including children who commit crimes. The crime of theft is the type of crime that most often occurs during people's lives that cause unrest. The form of theft committed by children in the Langkat Police jurisdiction is more dominant in the form of theft of oil palm fruit, as Langkat Regency has a large plantation area. 6,272 km², most of which are planted with oil palm trees, so that oil palm fruit becomes a valid object as an object of theft. The purpose of this study was to determine the factors causing the crime of theft of oil palm fruit committed by children, to determine the legal arrangements for the crime of theft of oil palm fruit committed by children, and to determine the law enforcement carried out by the Langkat Police for the crime of theft of coconut fruit palm oil by children. This research uses empirical juridical research and is analyzed qualitatively. The crime of stealing oil palm fruit committed by children is due to the influence of relationships in their environment, lack of parental attention, disharmony family relationships, economic influence, and the effect of the influence of children's education being low. The legal regulation of the criminal act of theft of oil palm fruit is regulated in Article 55 letter d, Jo. Article 107 of Law Number 39 of 2014 concerning Plantations, as every person is legally prohibited from harvesting and/or collecting plantation products, which is punishable by a maximum imprisonment of 4 (four) years or a maximum fine of Rp. 4,000,000,000.00 (four billion rupiah). Specifically regarding criminal threats against children as stipulated in Law Number 11 of 2012 that criminal threats for children are of the criminal threats of adults.